STRATEGI PERENCANAAN BISNIS DALAM USAHA KULINER UNTUK MEMENUHI PREFERENSI KONSUMEN LOKAL - Nofriser, Nofriser; Maurisni, Putri (Komunitas Manajemen Kompetitif, 2025)
This study aimsto explore culinary business strategy planning in Pasir Pangaraianby identifying consumer preferences that influence business decisions. The research method used was in-depth interviewswith 30 culinary business owners, which produced rich and relevant qualitative data. The findings show that understanding customer needsthrough continuous market research is very important inbusiness strategy planning. Factors such as product quality, competitive prices,and the atmosphere of the business premises have been proven to have a significant effect oncustomer satisfaction and loyalty. Additionally, menu innovation that respondsto trends and customer feedback, as well as staff training in customer service,are effective strategies for attracting and retaining customers.The implications of this research suggest that culinary business owners in PasirPangaraian focus on improving product quality and customer experiencethrough various innovative efforts. Thus, adaptive business strategiesthat are responsive to market dynamics can strengthen the competitiveness andsustainability of the culinary business in the region. This research providespractical insights for business actors in formulating the right strategies toface challenges in the culinary industry.